Study of the slow batch pyrolysis of mixtures of plastics, tyres and forestry biomass wastes. Effect of experimental conditions in the liguid compounds - Paradela, Filipe (2009)
In this work was studied the effect of experimental conditions in the production of liquid compounds from slow batch pyrolysis of mixtures of plastics, tires and pines wastes. The major compounds formed were toluene, ethylbenzene, and linear alkanes from C5 to C10 (each reaching yields around 5% w/w of the initial waste mixture). The pyrolysis reaction time and temperature improved the production of those species, while decreasing heavier alkanes formation. An increase of plastics content in waste mixture seemed to favour the production of lighter alkanes, although this effect was not as notorious as the ones just mentioned. The styrene production decreased regularly with the decrease of tyres content in the mixture. Autoclave initial pressure variation did not seem to affect significantly the formation of the major compounds.